Relasi Konsumen dengan Produk Kecantikan serta Pengaruhnya terhadap Purchase Intention - Purnamasari, Lathiyfah Shanti; Sutanto, Andi Heru; Angelita, Kezia; Setyarini, Ni Made Ari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The development of beauty industry has contributed to national economic growth. Apart from this large economic contribution, there are many social and psychological factors that influence this industry and cannot be separated from its economic factors. The article is written so that the beauty industry can see the relationship between consumers and beauty products that are psychologically built, both from external and internal factors, as well as from things that can be controlled by the beauty industry itself or from the superstructure of society. To reveal the relationship between consumers and beauty products, a qualitative study was conducted using the phenomenological method by collecting data using in-depth interviews with users of beauty products. The analysis used is the thematic meaning clustering and thematic structuring of the phenomena that occur. As a result, it was found that consumer relations with beauty products are strongly influenced by external factors, namely society beauty standards and internal factors, namely consumer skin problems. While things that affect the purchase intention of consumers of beauty products are price, effectiveness, comparison between price and effectiveness, function, packaging, texture, level of comfort, promo materials to access to these products.